2009
DOI: 10.1007/s10658-009-9443-1
|View full text |Cite
|
Sign up to set email alerts
|

Cercospora zeina is the causal agent of grey leaf spot disease of maize in southern Africa

Abstract: The aim of our study was to identify the causal agent of grey leaf spot disease of maize in southern Africa. Single-conidial cultures were recovered from maize leaves with typical disease symptoms sampled from several fields in South Africa, Zambia and Zimbabwe. Morphology, cultural characteristics, and a PCR-based test using Cercospora zeae-maydis and C. zeina-specific primer sets identified all single-conidial cultures as C. zeina. In addition, sequence alignment of DNA fragments of the internal transcribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 23 publications
4
56
0
Order By: Relevance
“…African and US group type II populations were co-specific with limited variability and type II species grew much slower and did not produce any toxins in culture. Crous et al (2006) and Meisel et al (2009) reclassified group type II as distinct species now called Cercospora zeina endemic in African countries. Okori et al (2003) confirmed the widespread presence of type II biotypes in East Africa (Kenya, Uganda, and Rwanda) and indicated that gene flow was high among African populations of C. zeaemaydis.…”
Section: Grey Leaf Spot Caused By Cercospora Zeae-maydismentioning
confidence: 99%
“…African and US group type II populations were co-specific with limited variability and type II species grew much slower and did not produce any toxins in culture. Crous et al (2006) and Meisel et al (2009) reclassified group type II as distinct species now called Cercospora zeina endemic in African countries. Okori et al (2003) confirmed the widespread presence of type II biotypes in East Africa (Kenya, Uganda, and Rwanda) and indicated that gene flow was high among African populations of C. zeaemaydis.…”
Section: Grey Leaf Spot Caused By Cercospora Zeae-maydismentioning
confidence: 99%
“…CPC 12062 were obtained from the culture collection of the Centraalbureau voor Schimmelcultures, Utrecht, The Netherlands. The C. zeina cultures CMW 25463, CMW 25467, CMW 25445, CMW 25442, CMW 25459, CMW 25465, CMW 25462, CMW 25454, CMW 25452 and CMW 25466 are described in Meisel et al 2009. Fungal cultures were grown on V8 medium (800 ml of distilled water, 200 ml of V8 juice, 15 g of agar, and 2 g of CaCO 3 ) in the dark at 25°C.…”
Section: Biological Materials and Host Plant Infectionmentioning
confidence: 99%
“…Leaf samples were taken 15 weeks after planting from nine individual plants from each line that were positioned randomly within a field site situated in Kwazulu-Natal Province, South Africa. Grey leaf spot disease is prevalent in this region, and therefore the plants were exposed to a natural inoculum of C. zeina (Meisel et al, 2009). A 12 cm length of the leaf immediately above the lowest cob from each plant was marked with a permanent black marker pen.…”
Section: Biological Materials and Host Plant Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the two groups were determined to be taxonomically distinct species; Group I retained the species name of C. zeaemaydis, whereas Group II was designated C. zeina (Crous et al, 2006). Interestingly, C. zeina appears to be the predominant (if not exclusive) gray leaf spot pathogen in Africa (Dunkle and Levy, 2000;Meisel et al, 2009). Both fungi causes distinctive rectangular lesions delineated by major veins of the leaf, and the disease derives its name from the grayish appearance of lesions when masses of conidia are produced on erumpent conidiophores emerging from stomata.…”
Section: Cercospora Zeae-maydis Causes Gray Leaf Spot Of Maizementioning
confidence: 99%